How to Better Motivate Customers to Participate in the Self-Design Process: A Conceptual Model in Underlying Self-Congruence Mechanism - Yu, Baojun; Xu, Hangjun; Emery, Brooke (Frontiers in Psychology, 2020)
The voluntary shift of responsibility from the producer to the consumer is one feature of self-design activities. Past research emphasizes the economic gains of such customer co-creation. However, the psychological mechanism underlying customer co-creation behavior is still not fully understood. Notably, the goal-driven self-congruence nature of customer co-creation is mostly ignored in the co-creation literature. The objective of this research is to firstly develop a conceptual understanding of how co-creation literature can be related to the self-congruence theory. Furthermore, this study also extends the original self-congruence theory by arguing the differential role of actual and ideal self-congruence on the relationship between self-congruence and customers’ willingness to participate in the co-creation process. Two laboratory experiments were conducted to examine whether self-congruence plays a prominent role in motivating customers to participate in the self-design process. Specifically, both the actual self-congruence and ideal self-congruence are positively related to customers’ willingness to participate in the self-design process is hypothesized. Moreover, it is expected that product styles and different consumption situations may strengthen the relationship between actual/ideal self-congruence and customers’ willingness to participate in the self-design process. Theoretical and practical implications are also discussed.